Progress of Stem Cell Transplantation for Treating Myocardial Infarction - Chen, Zhi; Zeng, Chunyu; Wang, Wei E. (Current Stem Cell Research & Therapy, 2017)
Background: Despite optimal treatment, myocardial infarction (MI) remains a major cause of death worldwide. Stem cell transplantation, as a promising therapy hoping to improve myocardial function and generate new myocardium, has been intensely studied for treating MI. Objective: To summarize the recent advance of stem cell transplantation for treating MI in clinical trials and preclinical studies. Results: Several types of adult stem cells have been applied to clinical trials and exerted beneficial effects against MI. The therapeutic effects of these stem cells are varied, modest and mostly depend on paracrine function. Embryonic stem cells and induced pluripotent stem cells, as well as their derivative cells, bring a new dawn for cardiac regeneration although they have not been applied in patients due to safety concerns. Feasible solutions are required to stress the safety issue, and to improve the survival, engraftment, migration, differentiation and synchronization with recipient myocardium of transplanted stem cells. Conclusion: Stem cell transplantation for treating MI in clinical trials has achieved modest therapeutic effect. The hurdles limiting the stem cell function define the direction of further research.
Keywords: myocardial infarction